(untitled) (Global Journal of Management and Business Research, 2023)
Promotional activities destine the future of your business Once Beth Comstock says You can t sell anything if you can t tell anything The thriving of your business totally depends on how you present your products Long since there various types of marketing methods have been used from time to time But in modern times the channel of marketing and promotional activities started to rely on Digital Marketing Because it s way easier to get in touch with collect feedback and real-time communication with customers